India's economic development since independence: An interpretative survey - Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
When India became a republic in 1950, the economy was primarily agrarian, with threefifths of output originating from agriculture. In the sixty years since independence, there has been a significant transformation of economic activity away from agriculture, with less than one-fifth of output now originating from agriculture and the rest from manufacturing and services. Since the 1980s, along with structural change, there has been strong economic growth, till 2010, followed by a period of declining growth. In this paper, we describe India's economic foundation, paying particular interest to the processes of economic growth and structural change. We begin with a brief discussion of the patterns of growth and structural change since independence. We then discuss the economic policies that have underpinned India's economic development. Next, we discuss the evolution of the three main economic sectors-agriculture, industry, and services. We then provide a summary of India's regional performance. We end with a discussion of India's economic performance in the post-2014 period.
Keywords: O10; O53; P27; 330; economic growth; structural change; economic policy; India